Germany: Germany country drug report 2019 (European Monitoring Centre for Drugs and Drug Addiction, 2019)
"This report presents the top-level overview of the drug phenomenon in Germany, covering drug supply, use and public healthproblems as well as drug policy and responses. The statistical data reported relate to 2017 (or most recent year) and areprovided to the EMCDDA by the national focal point, unless stated otherwise"